VLBI Observations of Southern Hemisphere ICRF Sources. II. Astrometric Suitability Based on Intrinsic Structure - Ojha, Roopesh; Fey, Alan L.; Charlot, Patrick; Jauncey, David L.; Johnston, Kenneth J.; Reynolds, John E.; Tzioumis, Anastasios K.; Quick, Jonathan F. H.; Nicolson, George D.; Ellingsen, Simon P.; McCulloch, Peter M.; Koyama, Yasuhiro (IOP, 2005)
We present 8.4 GHz very long baseline interferometry (VLBI) observations of 48 southern hemisphere extragalactic sources from the International Celestial Reference Frame. These are the second in a series of observations intended to image all such sources in the southern hemisphere at milliarcsecond resolution and bring the total number of observed sources to 111. We use these data, together with previously published data, to quantify the magnitude of the expected effect of intrinsic source structure on astrometric bandwidth synthesis VLBI observations by calculating a "structure index" for the sources; the structure index yields an estimate of their astrometric quality. Approximately 35% of sources in our sample have a structure index indicative of compact or very compact structures. The remaining two-thirds of our sources are less compact and should probably be avoided in astrometric and geodetic VLBI experiments requiring the highest accuracy unless intrinsic source structure can be accounted for in the astrometric/geodetic analysis.